Incisions / Insertions: re-inscribing narrative into a city landscape - Comninos, Alexia (School of Architecture, Planning and Geomatics, 2017)
Dating back to the late 1700's from the skirt of Devil's Peak down to what used to be the shoreline of Cape Town, this once walled off city has undergone plentiful re-inscriptions of the landscape till today. Remnants of the old French line fortifications remain along the slope of Trafalgar Park, disregarded and lost in the city 'scapes. The reading and re-tracing to pre-existing and existing layers of the precinct has been developed through blackout art methods of incisions and insertions to acknowledge the pre-existing and the existing in order to create a new narrative for this land without a landscape. In establishing the character of the narrative and the architecture thereof, the imagination of the space transcribed from archetypes - people - from the surrounds and what could be their ultimate feeling for what should be placed forms the landscape and how their individual expectations meet with others. The narrative is split twofold, the one is that the moments along the Bigger story is the park intervention - traces of the incision old fort wall - strung into the city block and the other is the pedestrian insertion armature which cuts through the site, providing for a short cut to the train station. The path aims to take the pedestrian through a series of spatial experiences through the site. These experiences are shaped by the tectonic expression. The architecture of the new is at constant dialogue with the existing, playing on a series of incisions and insertions. The cross pollination of the varying programme in the precinct facilitates this dynamic spatial experience through the link.